ARCHITECTURE IS NOT ONLY A MEANS OF CONSTRUCTING STRUCTURES AND EXPRESSING ARTISTIC AND AESTHETIC VALUES (Multidisciplinary Journal of Science and Technology, 2026)
Modern architecture and art are considered important and interrelated fields today. Architecture is not only the construction of buildings but also a means of expressing artistic and aesthetic values closely connected with art. This article analyzes the relationship between modern architecture and art, their mutual influence, innovative projects, and new forms of artistic expression